Evaluasi Keragaman Genetik Generasi Pertama (F-1) Cendana Santalum album Linn. Umur 4 Tahun di Kabupaten Gowa, Sulawesi Selatan - Mir Alam; Abd. Qudus Toaha; Abd. Kadir Bunga; Juhriah Juhriah (Universitas Hasanuddin, 2023)
A Sandalwood Santalum album Linn. is a type of plant native to East Nusa Tenggara, is a prestigious species, as an expensive and luxurious commodity, contains essential oils with a distinctive odor, wide potential uses that triggers exploitation of this species. This study aims to: know the variations in the growth of the parent trees, and the adaptability of sandalwood, Identify genetic and phenotypic correlations between growth parameters, Estimate heritability values on growth parameters, Estimate genetic gain sandalwood F-1 (4-year-old) in test plots Gowa Regency South Sulawesi. This study used a randomized block design consisting of 36 parents trees, 4 tree plots, 4 blocks, a spacing of 4 x 2 m. The results showed that there was genetic variation between the parents plants tested. The mean growth rates for height, diameter, volume, and crown width were 3.05 m, 5.68 cm, 8.40 m3, and 2.40 m, respectively. The estimated individual heritability values of the high parameters, and the canopy of 0.51 and 0.41 are categorized as high, but for the estimated heritability values of the parent trees, namely 0.50 and 0.44, they are in the medium category, 4 other parameters are included in the low category (smaller than 0.4 ). Genetic and phenotypic correlations ranged from 0.15–0.94 and -0.013–0.089, respectively. Selection intensity of 50% on the parameters of height and diameter of stem resulted in a genetic gain of 11.72% and 4.02%. The best ranking on parents tree number 48 with an index value of 21.23.